Oxide inclusions in austenitic/lean duplex stainless steels joined by flux-cored arc welding - Suphitcha Moonngam (2020)
© 2020, Chiang Mai University. All rights reserved. 2101 and 2304 lean duplex stainless steels have been developed and represented as alternatives to 316/316L austenitic stainless steels. In this research, 2101 and 2304 were joined by the Flux-cored Arc Welding process (FCAW) with E2209 filler metal with different shielding gases. The oxide inclusions in the weldments under different shielding gases, which were pure CO2 and mixed (20%CO2 and 80%Ar) shielding gases were investigated in detail by the Scanning Electron Microscope (SEM), and analyzed by using Image-Pro software. The quantitative data of size distribution was analyzed by histogram distribution plots. The chemical compositions of oxide inclusions were determined by Energy Dispersive X-ray spectroscopy. Microstructures of weldjoints were observed in three different zones: base metal (BM), heat-affected zone (HAZ), and fusion zone (FZ), respectively. The oxide inclusions were detected in the fusion zone with a uniform distribution. The average diameter of oxide inclusions was 0.76±0.51µm welded under pure CO2 shielding and 0.65±0.45µm under mixed (20%CO2 and 80%Ar) shielding gases. There were no significant differences in oxide inclusion for both shielding gases. In addition, the size distribution in both shielding gases indicated normal distribution in a range of 0.479-0.714µm. The oxide inclusions were identified as the Si oxide and O-Ti-Mn-Cr type oxides, less than 1.5area% in the fusion zone. The analysis of those oxide inclusions will be discussed in details.